Pengaruh Waktu Pemupukan pada Dua Musim Tanam terhadap Karakter Wijen Sbr-1 dan Sbr-3 di Lahan Pasir Pantai - Dewi Ratna Nurhayati; Prapto Yudono; Taryono Taryono; Eko Hanudin (Caraka Tani: Journal of Sustainable Agriculture, 2018)
Sesame is recognized as healthy potential oil crops because can be used to control several diseases. Sesame can grow properly in light soil structure such as sandy coastal soil, however sandy soil is considered as unfertile one and therefore environmental friendly fertilizer application based on dung manure must be studied. The research toinvestigate the influence of application times of mixed fertilizer on the growth sesame in quality growth in coastal sandy soil both at rainy and dry seasons, therefore the experiment directly to the sandy field at the sandy coastal area of Keburuhan, Purworejo, Central Java. From the first stage, it could be said that the application of mixed fertilizer between chicken manure and inorganic fertilizer increasing tochlorophyll content, net assimilation rate, root volume sesame both in rainy and dry seasons.